2022
DOI: 10.1038/s41598-022-11233-5
|View full text |Cite
|
Sign up to set email alerts
|

Left atrium phasic impairments in paroxysmal atrial fibrillation patients assessed by cardiovascular magnetic resonance feature tracking

Abstract: Atrial fibrillation (AF) is an abnormal and irregular heartbeat caused by uncoordinated electrical impulses in the left atrium (LA), which could induce lasting changes in the heart tissue or could be a consequence of underlying cardiac disease. This study aimed to assess the left atrial phasic function and deformation in paroxysmal AF (PAF) patients—who had not received radiofrequency ablation and had no signs of permanent AF—using the cardiovascular magnetic resonance (CMR) feature-tracking (FT) technique. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…ht was constructed by applying the Reynolds transport theorem 58 to Equation (1) and solving for ht, to give: ht=[]∂Ωbold-italicFbold-italicn0.1emnormaldS1dVLAtdt. Here, Ω denotes the domain boundary, n is the surface normal vector, and dVLA/dt is the rate of change in LA volume. We considered two scenarios; one where the temporal volume change was based on a generic LA volume curve obtained from the existing literature, 59 and one where this specific rate of change was obtained from the time‐resolved CT images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ht was constructed by applying the Reynolds transport theorem 58 to Equation (1) and solving for ht, to give: ht=[]∂Ωbold-italicFbold-italicn0.1emnormaldS1dVLAtdt. Here, Ω denotes the domain boundary, n is the surface normal vector, and dVLA/dt is the rate of change in LA volume. We considered two scenarios; one where the temporal volume change was based on a generic LA volume curve obtained from the existing literature, 59 and one where this specific rate of change was obtained from the time‐resolved CT images.…”
Section: Methodsmentioning
confidence: 99%
“…Here, ∂Ω denotes the domain boundary, n is the surface normal vector, and dV LA =dt is the rate of change in LA volume. We considered two scenarios; one where the temporal volume change was based on a generic LA volume curve obtained from the existing literature, 59 and one where this specific rate of change was obtained from the time-resolved CT images.…”
Section: Wall Boundary Conditionsmentioning
confidence: 99%
“…Moreover, in a study conducted on patients with different degrees of diastolic dysfunction, it was shown that LA volumes, and impaired LATF, LAS-r, and LAS-a were significantly associated with the severity of diastolic dysfunction [ 80 ]. Similarly, another study proved that LA phasic function determined by CMR might provide important subclinical information regarding LA remodeling in patients who develop paroxysmal atrial fibrillation [ 81 ].…”
Section: Assessment Of La Function By Cardiac Functional Imagingmentioning
confidence: 99%
“…Two software programs were used for image processing: Image Arena (2D CPA MR, TomTec Imaging Systems GmbH, v4.6.4.40) and cvi42 (v5.13.9, Circle Cardiovascular Imaging). The left atrium (LA) was analyzed in Image Arena as described previously [20]. The parameters included the minimum LA volume index (LAVImin), maximum LA volume index (LAVImax), and LA volume index before LA contraction (LAVIpac).…”
Section: Cmr Data Analysismentioning
confidence: 99%